The Effect of Concomitant Tricuspid Valve Regurgitation on the Condition of Patients with Ischemic Mitral Insufficiency - Rudenko, S. A. (Ukrainian Journal of Cardiovascular Surgery, 2020)
Ischemic mitral regurgitation is one of the most difficult and complex problems of surgical treatment of coronary heart disease and drug therapy of this group of patients. Mitral regurgitation in coronary heart disease negatively affects the survival of patients. The combination of ischemic mitral regurgitation and tricuspid valve insufficiency significantly worsens the prognosis in this category of patients. The aim. To study the effect of concomitant tricuspid insufficiency on the condition of patients with ischemic mitral regurgitation. Material and methods. From January 2012 to December 2019, 292 patients with ischemic mitral insufficiency underwent surgical intervention at the National Amosov Institute of Cardiovascular Surgery of the NAMS of Ukraine. Results and discussion. Almost half of the patients (48.0%) who applied to the Institute and had severe tricuspid valve regurgitation already had a history of moderate right atrial hypertrophy. In the expressed backflow on the tricuspid valve these blockades occur much more often than in the absence of insufficiency of the tricuspid valve (p<0.01). The occurrence of ventricular and atrial extrasystoles is also not reliably linked to the level of tricuspid valve regurgitation. Examining the results of surgical treatment of patients with mitral regurgitation of ischemic origin revealed positive correlation between the effect of tricuspid valve regurgitation and postoperative mortality. Examining the results of surgical treatment of patients with mitral regurgitation of ischemic origin revealed positive correlation between the effect of tricuspid valve regurgitation and postoperative mortality. Conclusions. Concomitant tricuspid insufficiency in mitral regurgitation of ischemic origin significantly affects clinical condition of patients and their quality of life. The results of surgical treatment of patients with ischemic mitral regurgitation also depend on the degree of preoperative tricuspid valve regurgitation.